2015
DOI: 10.12659/msm.892593
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral versus Bilateral Pedicle Screw Fixation for Degenerative Lumbar Diseases: A Meta-Analysis of 10 Randomized Controlled Trials

Abstract: BackgroundThe common and effective treatment for degenerative lumbar diseases is lumbar spinal fusion. Controversy still exists on the choice for instrumentation with spinal fusion procedures. Therefore, we conducted this meta-analysis exclusively of RCTs to compare the clinical outcomes of patients receiving bilateral versus unilateral pedicle screw fixation (PSF).Material/MethodsAfter systematic review of published and unpublished literature, a meta-analysis was conducted to compare the 2 treatment strategie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…In our study, based on an average of 2.5 years follow-up, interbody fusion rates were 96.7%, 96.8%, and 94.1% in the UPSFB group, BPSFB group, and BPSFC group, respectively, and there was no significant difference among the 3 groups regarding interbody fusion rate. Similarly, a recent meta-analysis of RCTs reported fusion rates of 90.6% (230/254) and 94.0% (251/267) in unilateral and bilateral pedicle screw fixation groups, respectively, which were not significantly different [ 1 ]. In another study, fusion rates were 92.2% (249/270) in the unilateral group and 96.0% (264/275) in the bilateral group, without significant difference [ 10 ], and there was no significant difference among the 3 surgical procedures in reoperation rate and patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, based on an average of 2.5 years follow-up, interbody fusion rates were 96.7%, 96.8%, and 94.1% in the UPSFB group, BPSFB group, and BPSFC group, respectively, and there was no significant difference among the 3 groups regarding interbody fusion rate. Similarly, a recent meta-analysis of RCTs reported fusion rates of 90.6% (230/254) and 94.0% (251/267) in unilateral and bilateral pedicle screw fixation groups, respectively, which were not significantly different [ 1 ]. In another study, fusion rates were 92.2% (249/270) in the unilateral group and 96.0% (264/275) in the bilateral group, without significant difference [ 10 ], and there was no significant difference among the 3 surgical procedures in reoperation rate and patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Lumbar pedicle screw fixation and interbody fusion is a commonly used and effective surgical method to treat single-level lumbar degenerative diseases (LDD), such as spondylolisthesis, discogenic pain, and lumbar spinal canal stenosis associated with deformities [ 1 , 2 ]. Bilateral pedicle screw fixation and interbody fusion with cage (BPSFC) is widely used for managing lumbar spinal fusion [ 3 – 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although MIS-TLIF is widely performed with the treatment of DLD, the choice for instrumentation with spinal fusion procedures remains controversial. In general, bilateral pedicle screw (BPS) fixation for MIS-TLIF is preferred as a standard procedure due to its rigid fixation, great biomechanical stability and good clinical results [ 9 , 10 ]. However, some studies have indicated that increased number of implants and excessive rigidity can lead to more adverse clinical effects, such as reducing fusion rate and adjacent segment degeneration [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dual column fixation is considered to be important for joint stability and early mobilization in surgery [11,12]. We designed a plate-screw fixation model for both fractured columns of the acetabulum.…”
Section: Discussionmentioning
confidence: 99%